Inteligencia Artificial y Seguridad. Dilemas de Confianza o Desconfianza para una Bioética y Biopolítica de Contención - Barrero, David (Hemisferio - Revista del Colegio Interamericano de Defensa, 2020)
The development of Artificial Intelligence opened new doors to the well-being and development of human beings; automating tasks, improving health services, reducing errors, streamlining production processes and helping you to discover new worlds, among many others. However, bioethical dilemmas and concerns arise when the reach of Artificial Intelligence is not equitable and equal for everyone on the planet, opening gaps between the worlds; the western hemisphere being one of those affected every day, even if with global consequences. Furthermore, the traditions and new threats, as well as the concerns and challenges of multidimensional security multiply with the incorrect use of Artificial Intelligence by those who seek to affect human beings themselves; even with the intention of creating robotics that can replace and displace man, putting human life and survival at risk. This implies the need to expand the complexity of security, global bioethics and biopolitics, in order to contain risks to the human species and nature in general.